NEW MATHEMATICAL FINDINGS BY SECONDARY STUDENTS - Quesada, Antonio R.; Department of Mathematics and Computer Science. The University of Akron, Akron Ohio, EE.UU. (Pontificia Universidad Javeriana, 2013)
Dynamic geometry software is changing the way we teach and learn geometry. In this article, we review a selection of new results, published during thé last five years, which were found by secondary students using mostly this type of software. Some of these solutions represent new mathematical findings. The amount and depth of the problems solved in such a short time gives an idea of the potential for growth that technology, and in particular this software brings to the mathematics classroom.